Pengaruh Model Pembelajaran Conceptual Understanding Procedures (Cups) Dengan Pendekatan Saintifik Terhadap Aktivitas Dan Hasil Belajar Fisika - Aris Doyan; Gunawan Gunawan; Susilawati Susilawati; Rodi Atma Putra (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
This study aims to determine (1) the effect of CUPS learning model and direct learning, scientific approach, CUPS learning models and direct learning with the scientific approach to the activities and learning outcomes. This type of research is quasi-experimental with a 2x2 factorial design. The population is all students of grade X MIPA SMAN 1 Praya Tengah. Sampling using purposive sampling techniques consisting of students of class X MIPA 2 as the experimental class and class X MIPA 3 as the control class. Data obtained through tests of learning outcomes and learning activity through observation. Data were analyzed using Manova analysis. The results showed that (1) there are differences in learning activities and learning outcomes among students which taught by CUPS learning model and learners that taught by direct learning model; (2) there are significant scientific approach to the activity and learning outcomes; (3) there is interaction between the CUPS learning model with the scientific approach and direct learning with the scientific approach toward learning outcomes; and no interaction on learning activities.